Analysis of transient displacements for a ceramic–metal functionally graded cylindrical shell under dynamic thermal loading. Issue 9 (November 2015) - Zhang, Jing-Hua; Li, Guang-Ze; Li, Shi-Rong
Abstract: The transient displacements of a ceramic–metal functionally graded material(FGM) cylindrical shell subjected to dynamic thermal loading are investigated using the differential quadrature method (DQM). Firstly, the dynamic governing equations of the thin shell with simply supported edges under thermal loading are derived based on the classical shell theory, in which the material properties of the ceramic–metal FGM shells are assumed to be graded in the thickness direction according to a simple power law distribution in terms of the volume fractions of the constituents. Secondly, the transient temperature field of the ceramic–metal FGM is obtained by using the Laplace transform and power series method. Then, the transient displacements of the axisymmetric deformed shell are obtained by solving governing equations using the DQM. The effects of the shape geometry and the material constitutions on the transient central deflection are also analyzed. It is found that one could easily control the transient deformations of the FGM cylindrical shell under dynamic thermal loading by changing the volume fractions of the ceramics.